Multilingual composing on facebook: Defining the “Social” in social constructivism and social media - Hynes, Kathleen (Journal of Interdisciplinary Studies in Education, 2019)
Social constructivist theories underpinned nearly all of the seven empirical studies conducted on post-secondary English Language Learners’ (ELLs’) Facebook use. However, a potentially complicated relationship exists between the term “social” as education theorists conceive it and the adjective “social” used to describe online networking. Analysis shows that the former emerges from a paradigm that sees people’s interactions as capable of integration, while the latter refers to activities that tend to promote fragmentation. This suggests that transforming social media into a space for learning partly hinges on the instructor’s ability to design assignments that demand greater collaboration than Facebook asks of its users. Rather than abandoning SNSs, working within their limitations might create new opportunities for student engagement and learning.